Southern Pine Coneworm, Dioryctria amatella (Hulst) (Insecta: Lepidoptera: Pyralidae) - James R. Meeker (EDIS, 2005)
The southern pine coneworm, Dioryctria amatella (Hulst), also commonly referred to as a pitch moth, is consistently one of the most damaging insect pests of pine seed orchard crops throughout the southeastern United States (Ebel et al. 1980). Less well-recognized is that this widespread and frequently occurring insect also attacks a variety of other parts of pines (Pinus spp.) besides cones. Caterpillars can be found feeding on and in buds, male and female flowers, shoots, branches and stems of all ages and sizes, as well as in conelets (i.e., first-year cones) and second- year cones (Ebel 1965, Ebel et al. 1980, Goolsby et al. 1972). This document is EENY-325 (originally published as DPI Entomology Circular 393), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2004.